Effects of 2 different protocols of repeated-sprint training in hypoxia in elite female rugby sevens players during an altitude training camp - Bouten, J.; Brick, M.; Saboua, A.; Hadjadj, J.-L.; Piscione, J.; Margot, C.; Doucende, G.; Bourrel, N.; Millet, G. P.; Brocherie, F. (International Journal of Sports Physiology and Performance, 2023)
Objectives: Repeated-sprint training in hypoxia (RSH) is an effective way of improving physical performance compared with similar training in normoxia. RSH efficiency relies on hypoxia severity, but also on the oxidative-glycolytic balance determined by both sprint duration and exercise-to-rest ratio. This study investigated the effect of 2 types of RSH sessions during a classic altitude camp in world-class female rugby sevens players.